Modulating β-arrestin 2 recruitment at the δ- and μ-opioid receptors using peptidomimetic ligands. Issue 11 (7th September 2021) - Sharma, Krishna K.; Cassell, Robert J.; Meqbil, Yazan J.; Su, Hongyu; Blaine, Arryn T.; Cummins, Benjamin R.; Mores, Kendall L.; Johnson, David K.; van Rijn, Richard M.; Altman, Ryan A.
Abstract : C-Terminal modification of Leu-enkephalin analogs reduces β-arrestin signaling at the μ- and δ-opioid receptors. Such modifications will enable evaluation of novel signaling profiles for chronic pain management. Abstract : μ-Opioid receptor agonists provide potent and effective acute analgesia; however, their therapeutic window narrows considerably upon repeated administration, such as required for treating chronic pain. In contrast, bifunctional μ/δ opioid agonists, such as the endogenous enkephalins, have potential for treating both acute and chronic pain. However, enkephalins recruit β-arrestins, which correlate with certain adverse effects at μ- and δ-opioid receptors. Herein, we identify the C-terminus of Tyr-ψ[( Z )CFCH]-Gly-Leu-enkephalin, a stable enkephalin derivative, as a key site to regulate bias of both δ- and μ-opioid receptors. Using in vitro assays, substitution of the Leu 5 carboxylate with amides (NHEt, NMe2, N Cy Pr) reduced β-arrestin recruitment efficacy through both the δ-opioid and μ-opioid, while retaining affinity and cAMP potency. For this series, computational studies suggest key ligand–receptor interactions that might influence bias. These findings should enable the discovery of a range of tool compounds with previously unexplored biased μ/δ opioid agonist pharmacological profiles.